NUMERICAL MODELING OF APPLIED NEAR-SURFACE MOUNTED ON REINFORCEMENT SLAB WITH ABAQUS CAE - Irkhas Bayu Faveryan; Andreas Triwiyono; Suprapto Siswosukarto (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2023)
Reinforced concrete (RC) is the most applied material in modern construction. Research on strengthening RC concrete members has also been widely carried out. Over time, concrete elements might deteriorate due to several factors, such as load, creep, or any other environmental aspects, leading to stiffness or strength reduction. Following the rapid development of studies on RC, the development of strengthening of concrete structure Reinforced Polymer (FRP) is also the case to overcome concrete deterioration. To improve the strength capacity of the concrete beams, Ega (2020) investigated the effect of epoxy adhesive length on the bonding strength of rebar using several laboratory tests. The result of the study yielded that the optimum length for the epoxy was 150 mm with a strength increase of up to 165.3%. The laboratory tests were modeled numerically using Abaqus CAE to simulate the behavior of the RC beam. Investigating the ideal mesh size and crack model behavior was the first stage of modeling. An RC beam previously experimentally tested by Ega (2020) was used for validation. Therefore, this research compares the numerical results from the Abaqus simulation with experimental data results. The specimen tested for this research was a concrete beam of 1200 mm x 450 mm x 120 mm subjected to 3-point loading. This study aims to develop a suitable numerical model for one of the tested beams and facilitate the design of NSM that follows the character of the previous research.